Preceding haemorrhagic shock as a detrimental risk factor for respiratory distress after excessive allogeneic blood transfusion. Issue 1 (11th October 2017) - Masuda, R.; Iijima, T.; Kondo, R.; Itoda, Y.; Matsuhashi, M.; Hashimoto, S.; Kohira, T.; Kobayashi, N.; Okazaki, H.
Abstract : Background and Objectives: Whether transfusion‐associated circulatory overload arises as a simple result of over‐transfusion or requires another trigger remains unclear. Here, we examined whether respiratory distress could be reproduced by massive transfusion alone in an animal model. Materials and Methods: A total of 20 anaesthetized swine were equipped with monitors. Allogeneic blood was obtained from 10 donor swine. A 4‐stage loading protocol with each stage equivalent to 25% of the blood volume (BV) in the recipient swine was then used to infuse crystalloid (CR), hydroxyethyl starch (HES) or allogeneic blood (TR) ( n = 5 each). The five remaining animals were subjected to a haemorrhagic shock (HS) prior to an allogeneic blood transfusion (TRS). Results: The PaO2 /FiO2 (P/F) ratio did not decrease to the level of respiratory distress in either the CR group or the HES group after loading with a volume corresponding to 100% of the recipient BV. However, the TRS and TR groups exhibited significant reductions in the P/F ratio after fluid overloading (227 ± 29 and 267 ± 133, respectively). Blood transfusion after HS expanded the blood volume, but over‐transfusion alone did not. HS was accompanied by an increase in the white blood cell count. Conclusion: The lung and the heart can tolerate volume overloads with HES, CR and even transfused blood. However, a preceding HS may induce an inflammatory response, making the lung vulnerable to subsequent blood overloads. In this study, a preceding haemorrhagic shock mediated respiratory distress following massive transfusion in a swine model. (247 words)